2005
DOI: 10.1128/mcb.25.24.11102-11112.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for High-Capacity Bidirectional Glucose Transport across the Endoplasmic Reticulum Membrane by Genetically Encoded Fluorescence Resonance Energy Transfer Nanosensors

Abstract: Glucose release from hepatocytes is important for maintenance of blood glucose levels. Glucose-6-phosphate phosphatase, catalyzing the final metabolic step of gluconeogenesis, faces the endoplasmic reticulum (ER) lumen. Thus, glucose produced in the ER has to be either exported from the ER into the cytosol before release into circulation or exported directly by a vesicular pathway. To measure ER transport of glucose, fluorescence resonance energy transfer-based nanosensors were targeted to the cytosol or the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 36 publications
4
104
1
Order By: Relevance
“…However, it is probable that GLUT10 is not a single DAA/ glucose transporter in the endomembranes. Functional studies indicated the heterogeneity of glucose transport in the ER [19,20]. Moreover, it was also demonstrated that various GLUT transporters can sufficiently mediate glucose transport en route from the ER to the plasma membrane [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is probable that GLUT10 is not a single DAA/ glucose transporter in the endomembranes. Functional studies indicated the heterogeneity of glucose transport in the ER [19,20]. Moreover, it was also demonstrated that various GLUT transporters can sufficiently mediate glucose transport en route from the ER to the plasma membrane [21].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of GLUT10 in the endomembranes as a DAA and glucose transporter can be the molecular background of the functionally already observed transport activities [19,20,32]. However, it is probable that GLUT10 is not a single DAA/ glucose transporter in the endomembranes.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent nanosensors have also been developed for concentration-dependent sensing of maltose in yeast (Fehr et al, 2002), as well as for detecting glucose uptake and subcellular compartmentalization Fehr et al, 2005) or ribose uptake in mammalian cells. Furthermore, bimolecular fluorescence complementation (BiFC) can detect interaction between protein partners in living cells.…”
Section: Imaging Of Molecular Complexes In Living Cellsmentioning
confidence: 99%
“…In special cases, a priori knowledge can be used. For example, glucose concentrations in liver cells are known to be equilibrated by reversible GLUT-mediated plasma membrane transport (Fehr et al, 2005). Accordingly, intracellular glucose levels equal those in the extracellular space.…”
Section: Fluorescent Sensors For Time-lapse Microscopymentioning
confidence: 99%